2023
DOI: 10.1002/smll.202303498
|View full text |Cite
|
Sign up to set email alerts
|

Carbonized Platycladus orientalis Derived Carbon Dots Accelerate Hemostasis through Activation of Platelets and Coagulation Pathways

Pan Liang,
Tao Bi,
Yanan Zhou
et al.

Abstract: Achieving rapid and effective hemostasis remains a multidisciplinary challenge. Here, distinctive functional carbon dots derived from carbonized Platycladus orientalis (CPO‐CDs) are developed using one‐step hydrothermal method. The negatively charged surface of CPO‐CDs retains partial functional groups from CPO precursor, exhibiting excellent water solubility and high biocompatibility. Both rat liver injury model and tail amputation model have confirmed the rapid and effective hemostatic performance of CPO‐CDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The activity of factor VIII was increased from 54.6 ± 8.94% in the control group to 66.26 ± 11.00% in the TMP-CQDs-treated group, whereas no significant changes were found in factors IX, XI, and XII (Figure H–K). The TMP-derived carbon quantum dots retained some functional groups on their surfaces, which could have critical effects on platelets or cells through physical/chemical interactions. , All of these results indicated that the as-prepared TMP-CQDs could function as specific activators of factor VIII, which could further initiate the intrinsic coagulation pathway and finally lead to the activation of blood coagulation.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The activity of factor VIII was increased from 54.6 ± 8.94% in the control group to 66.26 ± 11.00% in the TMP-CQDs-treated group, whereas no significant changes were found in factors IX, XI, and XII (Figure H–K). The TMP-derived carbon quantum dots retained some functional groups on their surfaces, which could have critical effects on platelets or cells through physical/chemical interactions. , All of these results indicated that the as-prepared TMP-CQDs could function as specific activators of factor VIII, which could further initiate the intrinsic coagulation pathway and finally lead to the activation of blood coagulation.…”
Section: Resultsmentioning
confidence: 90%
“…The TMP-derived carbon quantum dots retained some functional groups on their surfaces, which could have critical effects on platelets or cells through physical/chemical interactions. 42,43 All of these results indicated that the as-prepared TMP-CQDs could function as specific activators of factor VIII, which could further initiate the intrinsic coagulation pathway and finally lead to the activation of blood coagulation.…”
Section: ■ Resultsmentioning
confidence: 95%
“…Here, the capacity of the nanocomposite hydrogel to stop wound bleeding was evaluated with the severed rat tail model (Figure S9, Supporting Information). [93,94] When compared to an untreated control, both PVA 15 /CD/HAG and PVA 15 /CD/HAG/ CD AgNP exhibited hemostatic properties with the latter one being the most performant. For instance, 0.1 g of the CD AgNP-containing nanocomposite hydrogel applied to the severed rat tail diminished bleeding by 55.5%.…”
Section: In Vivo Skin Wound Healing With Pva/cd/hag/ CD Agnp and Hemo...mentioning
confidence: 99%
“…One-third of the tail of an anesthetized animal was severed with surgical scissors as previously described. [93,94] Next, 0.1 g of hydrogel was immediately applied on the bleeding wound, which was then put in contact with a gauze. After completion of the hemostasis, the weight of the blood-soaked gauze was measured and the hemostatic time was recorded.…”
Section: Adhesivenessmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) is an important part of the prevention and treatment of hemorrhagic diseases [7][8][9]. The hemostatic mechanism of TCM is unique due to its multicomponent, multi-target and multi-pathway effects, as shown by modern research [10][11][12]. Panax notoginseng, the main component of Yunnan Baiyao, is a famous Chinese hemostatic medicine that can promote platelet aggregation to achieve rapid hemostasis [10].…”
Section: Introductionmentioning
confidence: 99%